Synthesis of field and satellite data to elucidate recent mass balance of five ice rises in Dronning Maud Land, Antarctica - Goel, Vikram; Morris, Ashley; Moholdt, Geir; Matsuoka, Kenichi (Frontiers in Earth Science, 2022)
We investigated mass balance changes over five ice rises in the last few decades near Fimbul and Nivl ice shelves in central Dronning Maud Land. We use the Input-Output Method constrained using field-based geophysical measurements conducted during the austral summers of 2012–14 over three ice rises near the Fimbul Ice Shelf. Further, we use satellite altimetry data (ICESat, ICESat-2, and CryoSat-2) to estimate geodetic mass balance over all five ice rises in recent decades. Both field- and satellite-based estimates show that until 2010, three out of five ice rises were thickening (0.4–0.2 mieq a-1) while two were close to balance. However, over the last decade, the ice rises thickening previously started to thin (-0.2–0.6 mieq a-1) while the other two remained close to balance. Much of this variability is likely associated with regional surface mass balance trends, with each ice rise exhibiting its characteristics depending on its local glaciological settings.